Evaluasi Kesesuaian Lahan Untuk Beberapa Tanaman Pangan Dan Perkebunan Di Kecamatan Burau Kabupaten Luwu Timur Sulawesi Selatan - IDA BAGUS SURYAWAN; I GUSTI PUTU RATNA ADI; I NYOMAN DIBIA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Evaluation Of Land Suitability For Several Food Crops And Plantations In Burau Sub-District, East Luwu Regency Of South Sulawesi This research aims to discover the actual and potential of land suitability, limited factor, improvement effort, land use management and the creation of land suitability mapsand direction of use for some food crops and plantations. Plants that are evaluated includerice, corn, chili, pepper, cocoa, clove and oil palm. The research was conducted in Burausubdistrict from February 2019 to June 2019. Based on the result overlapped of soil type,land use, and slope were obtained seven homogeneous land units. The research methodsused are surveys, analyses, and classification of land suitability based on the criteria ofgrowing plant requirements that are matched with the characteristics/quality of land.Results show that classes of actual land suitability for some food crops and plantations areS1 (very appropriate) until N (not appropriate). The limited factors in the research areainclude: temperature, rainfall, drainage, texture, CEC soil, base saturation, pH, C-Organic,N-Total, P2O5, K2O, slope, and the erosion hazard. Improvement of the land-suitabilityclass can be done with improvement effort except temperature and texture because theyare permanent barrier factor. Potential suitability class of land for some food crops andplantations evaluated are S1 (highly appropriate) until S3 (marginal appropriate), withlimited factors among others temperature, texture and slope factors. Land userecommendations on AISw, AIISw, AIKk, and AIKks are rice, corn and chili. AIIKks,PsIIIKk, and PsIVKks are recommended for pepper, cocoa, clove, and palm oil.